Rare Case of Multiple Perirenal, Extra-Adrenal Myelolipoma: Case Report, Current Management Options, and Literature Review - Goran Benko; Andrina Kopjar; Marin Plantak; Danijel Cvetko; Vicko Glunčić; Anita Lukić (Case Reports in Urology)
Extra-adrenal myelolipomas are rare, asymptomatic entities, although large tumors may cause local symptoms or hemorrhage. When these lesions occur outside the adrenals in the retroperitoneum, they are radiographically easily confused with both primary and secondary retroperitoneal tumors, which tend to be aggressive. Although myelolipomas are benign and can be managed conservatively, if malignancy is suspected, a surgical procedure is an option. We report a case of a 68-year-old patient with multiple perirenal extra-adrenal myelolipomas. Initial abdominal ultrasound reviled an inhomogeneous mass surrounding the left kidney. Subsequent CT examination of the abdomen showed four separate, extrarenal, well-circumscribed, round-shaped, fat-containing retroperitoneal tumors. Given the significant size of the masses, that compressed major abdominal vessels and the suspicion of liposarcoma, a surgical excision of the lesions was performed. The tumors were easily separated, all surrounding structures were spared, and they were removed completely. Histologically, all masses consisted of hematopoietic and mature fat tissue and the final diagnosis was extra-adrenal myelolipoma. The patient was released from the hospital 7th day after surgery in good condition and at his baseline. Since myelolipomas are, by definition, nonfunctional benign tumors, there was no need for further follow-up. The radiological evaluation and fine needle biopsy are usually sufficient to establish the diagnosis, but in some cases of well-differentiated liposarcoma, the differentiation between myelolipoma and liposarcoma can be challenging. Therefore, considering that myelolipomas and liposarcomas have opposite prognoses, which affects the surgeon’s decision on the extent of surgical procedure and further treatment, we also emphasize the importance of intraoperative assessment of the tumor, both by the surgeon and by intraoperative pathology consultation.